Pencegahan Stunting Melalui Pendidikan Kesehatan Gizi Serta Pola Hidup Bersih Dan Sehat Di Kampung Sobey Indah Distrik Teluk Duairi Kabupaten Teluk Wondama - Idris, Idris; Nursiah, Andi; Kasmiati, Kasmiati; Juniarti, Rizky Auliah; Fitri, Lidia; Jamin, Nunung Suryana (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a condition of malnutrition that is related to inadequate nutritional needs in the past, so it is a chronic nutritional problem. The habit of not measuring the height or body length of toddlers in the community makes it difficult to realize the incidence of stunting, so it becomes one of the focuses of the target for improving nutrition in the world until 2025. This Community Service activity aims to increase knowledge about stunting in an effort to prevent and reduce stunting, lifestyle health, nutrition for pregnant women, breastfeeding mothers, and feeding babies and children. Community Service activities are carried out using outreach methods regarding stunting prevention through nutritional health education and clean and healthy lifestyles. The result of Community Service is an increase in community knowledge and commitment to trying to implement a clean and healthy lifestyle as well as providing food for pregnant women, breastfeeding mothers, babies and toddlers according to recommendations.